Estética e sensações no jornalismo: um estudo das estratégias e jogos discursivos - Rocha, Paula Roberta Santana (2013)
Based on the observation that the study of affective manifestations can enable another interpretation position to the field of Communication, this dissertation seeks to work with the presence of aesthetics, sensations, emotions and affections immersed in the communication field, specifically in the universe of journalism. What interests us here is to understand, rather than the representative and intellectuals signs that constitute journalistic language, but mainly the powerful devices of affection and aesthetic whereby the language uses in the construction of its discourse. Thus, the main objective of this research is to perform a counterpoint between what, on one side we’ll name it aestheticized journalism, and in another, sensational or sensationalist journalism. Our main intent is to take emergency broader concept of aesthetics (like “faculty of feeling”) and link it to the practice of journalism to demonstrate that the communication field cannot be defined only by its operating instrumentality, but that other requirements as sensitivity and subjectivity are notoriously important for the construction of a journalism that integrates community and otherness . From another point, we take the concept of sensational journalism, or sensationalist journalism to demonstrate the dual facet that is the universe of sensation. For this, besides the elaboration of the theoretical framework , we will have support in the empirical analysis of two reports from Época magazine , using for this the Analysis of Discourse of the French line.